ANALISIS TERHADAP ANTESEDEN DARI GREEN PURCHASE INTENTION PRODUK BODY SHOP - Agung, Deatri Arumsari; Winarto, Evelyn; Junaedi, Marliana (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim : This study aims to determine what factors will influence the intention of the people of Surabaya to buy green products of the The Body Shop brand, by analyzing the constructs of environmental concern, environmental knowledge, green advertising, and green packaging. Design/Methode/Approach : This quantitative study uses primary data with a purposive sampling technique. Data to test the conceptual model were collected through an online survey targeting people in Surabaya who know about The Body Shop brand. A total of 150 responses were received and processed. The analysis tool used was partial least squares (PLS)–structural equality modeling (SEM). Research Finding : The results of this study indicate that environmental knowledge, green advertising, and green packaging have a significant correlation with the green purchase intention. In addition, it was found that the green packaging variable is the strongest factor in influencing people's intention to purchase green products compared to other determinants. Theoretical contribution/Originality : The unique contribution of this study is that this study is one of the first studies to investigate the combination of environmental motivation factors and green marketing elements on the green purchase intention. Practitioner/Policy implication : This study is very important for business, economics, and the government as a whole because it produces empirical evidence on how to develop green purchase intentions in the society. Research limitation : Further research should focus more on specific generations, such as gen Z, in an effort to examine their shopping behavior, and should be conducted in cities other than Surabaya to better represent consumer behavior in Indonesia.